Ink-jet printed In-Ga-Zn oxide thin film transistors - Wang, Ye. (2013)
Metal-oxide semiconductor is advantageous in terms of high mobility and stability, and has received great attention for thin film transistors (TFTs) application. Recently, In-Ga-Zn oxide (IGZO) is deemed as a good alternative channel layer material for TFTs, compared to conventional a-Si and poly-Si. It is transparent in the visible region due to the large band gap. It has a high mobility, even for an amorphous structure due to s-electron conduction. Up to now, most IGZO TFTs are fabricated by magnetron sputter and pulsed laser deposition, which require high vacuum condition, resulting in high cost. Ink-jet printed TFT technology is a low-cost alternative to conventional microelectronics process technologies. This technology is expected to result in many benefits. First, it is a low-waste and maskless process. Deposition and patterning are accomplished by ink jetting, reducing material usage and process complexity. In addition, ink-jet printing is amenable to roll-to-roll manufacturing fabrication on flexible substrate in the ambient condition. This renders more process flexibility, high overall throughput and ultra low cost. However, due to the development of the ink-jet printing electronic device fabrication is just at its beginning stage, this technology is rare to employ to fabricate IGZO TFTs. In this study, ink-jet printing method is applied to fabricate IGZO TFTs. We systemically investigate the influence parameters on the performance of printed IGZO TFTs in chapter 4, including gallium mole ratio, thickness of IGZO films, and post-annealing temperature. The results show that the field effect mobility and the threshold voltage are sensitive to these parameters. The shifting of threshold voltage is due to the carrier concentration changing, and the variation of the field effect mobility is related to the surface scattering and trap density. The best performance was obtained for the TFT with 55 nm IGZO thin films annealed at 500 oC for 1 hour in the air. It was operated in a n-channel enhancement mode with a field effect mobility in the saturation region of 1.41 cm2/V s, a threshold voltage of 1 V, a drain current on/off ratio of approximately 4.3 × 107, a subthreshold swing of 384 mV/dec and an off current level of lower than 1 pA.